Biomimetic Enamel Regeneration Using Self-Assembling Peptide P11-4 - Mohammad Alkilzy; Ghalib Qadri; Christian H. Splieth; Ruth M. Santamaría (Biomimetics, 2023)
The recent understanding of the etiology and pathology of dental caries has shifted its treatment from invasive drill and fill conventional strategies to noninvasive and/or minimally invasive approaches. Guided tissue regeneration (GTR) is a well-established therapeutic approach in medicine and periodontal and oral surgery. Recently, the concept of biomimetic regeneration has been further expanded to treat the loss of hard dental tissues. Self-assembling peptides have emerged as a promising biomaterial for biomimetic regeneration due to their ability to construct a protein scaffold in the body of early carious lesions and provide a matrix that promotes remineralization. This review article accompanies the development of self-assembling peptide P11-4 for the treatment of initial carious lesions. In vitro and in vivo studies on the safety, clinical applicability, and efficacy of P11-4 are discussed. Furthermore, different treatment options and potential areas of application are presented.